2014
DOI: 10.1590/0004-2730000002919
|View full text |Cite
|
Sign up to set email alerts
|

Celiac disease screening in Brazilian patients with osteoporosis

Abstract: Objective: To analyze if it is worthwhile to screen Brazilian osteoporotic patients for celiac disease (CD). Subjects and methods: One hundred patients with osteoporosis and 97 controls were evaluated for IgA-EmA (IgA anti-endomysial antibodies) by indirect immunofluorescence method and IgG-anti-tTG (tissue transglutaminase) by ELISA assay. Positive patients were invited to have gastrointestinal endoscopy with jejunal biopsy. Results: Two patients had positive IgG-anti-tTG test and one of them also showed posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…Our literature review identified eight relevant studies with a total of 3188 individuals with osteoporosis . Of these, 59 (1.9%) had CD.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our literature review identified eight relevant studies with a total of 3188 individuals with osteoporosis . Of these, 59 (1.9%) had CD.…”
Section: Resultsmentioning
confidence: 99%
“…When examining individuals with osteoporosis according to age at time of testing for CD, CD was somewhat higher in individuals tested at <60 years of age (1.8%; 1.3%‐2.3%), as compared to those ≥60 years (1.0%; 0.1%‐1.9%; Table ). Nonetheless, a meta‐regression analysis found no continuous relationship between age at testing and CD prevalence ( P = 0.917).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations